Experimental investigation of human tenability and sprinkler protection in hospital room fires. (4th August 2020) - Hostikka, Simo; Veikkanen, Eetu; Hakkarainen, Tuula; Kajolinna, Tuula
Summary: The effectiveness of sprinklers in protecting hospital patients in the room of fire origin was investigated by 14 experiments with a residential‐grade sprinkler system, and by two free‐burns. The fire load was UL 1626 corner fire. Tenability conditions were evaluated for the UL 1626 corner fire using gas temperature and species concentration measurements, and by calculating the fractional effective dose (FED) and fractional irritant concentration (FIC) with the comprehensive model of Purser and a more simplified method of ISO 13571. In the sprinklered tests, the average FED at 15 minutes was 0.8 ± 1 with 95% confidence, when using the Purser's method, and 0.2 ± 0.2 with ISO 13571. The difference was mainly caused by the assumption in the Purser's method that all NOx gases behave like NO2 . Ignoring the NO contributions decreased the Purser's FED values very close to those of ISO 13571. In nonsprinklered tests, the FED and FIC values indicated definite incapacitation and possibly death 3 minutes after ignition. The sprinklers effectively increase the possibility of surviving, but the toxic effects may still be dangerous. In hospital and health care environments, many of the exposed persons may have lower‐than‐average tolerance.